MORFOLOGI SPORA DAN PERKEMBANGAN GAMETOFIT Davallia denticulata dan Davallia trichomanoides - Meliza, Rezika; Chikmawati, Tatik; Sulistijorini, Sulistijorini (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2019)
Spore Morphology and Gametophyte Development of Davallia denticulata and Davallia trichomanoidesABSTRACTDavallia denticulata and D. trichomanoides are two attractive and decorative fern species for ornamental. Spore morphology has an important role in fern taxonomy, while media composition has important role in the growth and development of their gametophytes. Such information on the two fern species was lacking. Therefore, this study aimed to reveal the information of the spore morphology and gametophyte developmental stages of D. denticulata and D. trichomanoides on three different media. The spores were collected from Bogor, West Java. The spores were sown in three sterile media. Spore morphology and gametophyte development were observed under a stereoscopic microscope. Both gametophyte species reached their mature stage at 25 weeks after planting on the different media compositions. D. denticulata showed the best gametophyte development, and formed mature gametophytes on the media of vermiculite, sphagnum moss, and perlite, while D. trichomanoides grew best into maturity stage on the media containing vermiculite, and sphagnum moss. Thus, the presence of sphagnum moss in the media is an important material for the growth and development of Davallia gametophyte.Keywords: Davallia, development, gametophyte, growth, media  ABSTRAKDavallia denticulata dan D. trichomanoides merupakan dua spesies tumbuhan paku yang menarik dan indah untuk tanaman hias. Morfologi spora memiliki arti penting dalam taksonomi tumbuhan paku, sedangkan komposisi media berperan penting untuk pertumbuhan dan perkembangan gametofitnya. Informasi seputar hal ini terkait dua spesies tumbuhan paku tersebut belumlah ada. Penelitian ini bertujuan untuk mengungkap informasi mengenai ciri morfologi spora dan tahapan perkembangan gametofit D. denticulata dan D. trichomanoides pada tiga komposisi media berbeda. Pengambilan spora dilakukan di Bogor, Jawa Barat. Spora ditumbuhkan pada tiga media steril. Morfologi spora dan perkembangan gametofit diamati menggunakan mikroskop stereo. Kedua spesies memiliki waktu perkembangan terbaik untuk mencapai tahap gametofit dewasa yaitu 25 minggu pada komposisi media yang berbeda. D. denticulata berkembang dengan baik, dan membentuk gametofit dewasa pada media vermiculite, lumut sphagnum, dan perlite. D. trichomanoides berkembang hingga tahap gametofit dewasa dengan baik pada media vermiculite, dan lumut sphagnum. Dengan demikian keberadaan lumut sphagnum pada media sangat penting untuk pertumbuhan dan perkembangan gametofit Davallia.Kata Kunci: Davallia, gametofit, media, perkembangan, pertumbuhan